2017
DOI: 10.1007/s10484-017-9367-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Anxiety and Improving Academic Performance Through a Biofeedback Relaxation Training Program

Abstract: The aim of this study was to analyze the influence of a biofeedback relaxation training program on anxiety and academic performance. The program consisted of five biofeedback sessions coupled with three training activities focused on deep breathing, guided imagery, and muscle relaxation. The participants were second-year psychology undergraduates from the University of the Basque Country (UPV/EHU, northern Spain). The experimental group comprised 152 students (M = 19.6, SD = 0.74; 74% women) and the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
3
39
1
4
Order By: Relevance
“…Music makes one able to express themselves freely, and music can make people smarter, reduce memory, reduce creativity, nourish the body, reduce emotional intelligence, etc. Furthermore, this findings are consistent with systematic desensitization techniques and behavioral techniques can reduce exam anxiety in students (Otta & Ogazie, 2014), biofeedback relaxation training reduce anxiety and improving academic performance (Aritzeta et al, 2017), and the combination of relaxation technique with cognitive behaviour therapy optimizes academic performance (Akinsola & Nwajei, 2013).…”
Section: Measurement Experiments (N=18)supporting
confidence: 75%
See 1 more Smart Citation
“…Music makes one able to express themselves freely, and music can make people smarter, reduce memory, reduce creativity, nourish the body, reduce emotional intelligence, etc. Furthermore, this findings are consistent with systematic desensitization techniques and behavioral techniques can reduce exam anxiety in students (Otta & Ogazie, 2014), biofeedback relaxation training reduce anxiety and improving academic performance (Aritzeta et al, 2017), and the combination of relaxation technique with cognitive behaviour therapy optimizes academic performance (Akinsola & Nwajei, 2013).…”
Section: Measurement Experiments (N=18)supporting
confidence: 75%
“…The stimulus that produces anxiety is repeatedly paired with relaxed exercise until the relationship between incentives and responsiveness to anxiety disappears. The research study recognizes that systematic desensitization that strengthens the assumptions above are: research found that systematic desensitization techniques and behavioral techniques can reduce exam anxiety in students (Otta & Ogazie, 2014), biofeedback relaxation training programs in educational contexts could be a way of reducing anxiety and improving academic performance (Aritzeta et al, 2017), and another findings confirm the effectiveness and efficacy of cognitive therapy in managing anxiety and depression and improving academic performance, and when combined with relaxation technique, the combination optimizes academic performance (Akinsola & Nwajei, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…These results were opposite to the initial hypothesis, showing the influence of autonomous modulation in academic performance of students, but future studies with a larger sample must delve in this line for better knowledge of this complex relation. An appropriate autonomic nervous system regulation promotes a healthier general state, that, joining a higher emotional control, better self-efficacy conception and self-confidence, would prepare students for the incoming academic challenges [73,74]. These tools are basic to develop stress control abilities, reducing anxiety states in high academic demand moments, and strengthening student's self-knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Such impairment has been explained through a reduction of the processing capacity available for cognitive evaluation (Sanbonmatsu & Kardes, 1988). In the same vein, students with high levels of test anxiety perform worse on tests, and their overall academic achievement is lower (Aritzeta et al, 2017). Test anxiety, located in the high arousal, negative valence area, has been shown as the academic emotion most often reported by the students and can reduce working memory resources (Pekrun et al, 2002).…”
Section: Arousal and Performancementioning
confidence: 99%